O silêncio na música: uma investigação formal e de performance em obras para violoncelo e piano dos períodos Clássico e Romântico - Bielschowsky, Pedro Henrique Carvalho (2019)
Though a topic of relatively scarce studies, silence in music is a fascinating component of the music composition as well as to the musical interpretation universe. The main topic of this study is the silence as an element of musical expression, more deeply, regarding the theory and practice of silence in this universe, through examining a selection of the Classic and Romantic cello repertoire. It also presents a mapping of contemporary theories for concert music on functions and qualities of silence in music, with emphasis on the contributions from authors such as Braman (1956) and Margulis (2007b), as well as relevant music concepts coined by Cone (1968) and Epstein (1995) The empirical part of the thesis presents the perception of twenty-eight renowned performers on their understanding and approaches on the topic. It is analysed whether the interviewees have singular approaches, noticing if the outcome is a source of intuition and improvisation, or rather a reflection of mindful, careful, and permanent use. This work studies the ways musicians reflect beyond the knowledge presented by theorists in subjects such as: flexibility in the duration of a pause, specifically when the notation on the score does not necessarily show it (comas, fermata, etc.); application of silent intersections by performers, even when not instructed by composers in music notation; the function of silence prior or subsequently to the musical performance; gesture and its relation to silence; a specific way of feeling the pulse; acoustics conditions that may influence the performance, and the perception of silence in music; as well as extra musical elements that may affect the impact of silence during the performance. The theoretical hypotheses and interpretative approaches on silence in music compositions are organized accordingly to four moments: pre-performance, post-performance, silence between movements, and the various forms of interpreting silence is inserted within the musical discourse, and how these four aspects of silence influence the construction of musical interpretation.